(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2021)
Iodotherapy is a complementary treatment to thyroid resection surgery, being performed with radioactive iodine (131I). To do the treatment, the patient must be hospitalized due to the exposure of other people to the ionizing radiation emitted by the radiopharmaceutical. The patients’ hospitalization time is dependent on the activity of radioactive material administered and may be from one to two days. After the patient´s discharge from hospital, another one may be hospitalized, however, the room must be monitored by the technical staff in order to verify whether there is radioactive contamination due to the previous patient. Thus, the present study aims to verify the dose received in the staff´s thyroid region during the monitoring of the therapeutic room after discharge, since the thyroid is one of most sensitive to iodine. Two occupationally exposed staffs (called “V1” and “V2”) were monitored using TLDs positioned in the thyroid region. V1 and V2 were monitored for 7 months and 3 months, respectively, because of the workflow of the clinic where the research was performed. With the doses received, during these periods, it was estimated that the annual doses received by V1 and V2 were, respectively, (11.2 ± 5.2) mSv and (12.7 ± 1.0) mSv. These results are below the dose limits established by the ICRP and other international guideline, which reveals that the research clinic is concerned with occupational radiation protection and no other radiological protection actions, based on the thyroid exposure, are necessary.